PEMBERIAN AROMATERAPI PEPPERMINT KEPADA PASIEN HD DI RSU SEMBIRING DELI TUA - Friska Br Sembiring; Reisy Tane; Lily Suryani (INSTITUT KESEHATAN DELI HUSADA, 2021)
Uremic pruritus is one of the complaints that often occurs in patients with chronic renal failure which is an uncomfortable sensation or itching and can cause disturbances during the day or night and can even occur throughout the day such as sleep disturbances, activity, depression and skin complications that can reduce quality of life for patients with chronic renal failure. Patients undergoing hemodialysis therapy will be faced with a variety of health status disorders, one of the most common complications is uremic pruritus (UP) with a multi-factor cause. The intensity and spatial distribution of pruritus were highly significant over time and patients varied to a greater extent and were influenced by the duration of renal impairment. This health education is to provide information about the benefits of peppermint in reducing uremic pruritus experienced by patients with chronic renal failure. This health education provides information about the benefits of peppermint in reducing uremic pruritus experienced by patients with chronic renal failure. This counseling was conducted at the Sembiring Deli Tua General Hospital. This counseling provides some information on the factors that cause and exacerbate the incidence of uremic pruritus in patients with chronic renal failure so that nurses can be more optimal in providing nursing care for patients with uremic pruritus, especially in patients with chronic renal failure.